Contextualización histórica del concepto de paisaje, sus implicaciones filosóficas y científicas - Castillo Poveda, Manuel Alejandro (2017)
In order to generate a better understanding of what encompasses the concept of landscape in social sciences, we will undertake a journey from its origins to the present, addressing figures, trends, politics, philosophy and context that participated in its development; generating a picture of this term in the constitution of scientific discourse.